Movement patterns of the iconic giant kingfish Caranx ignobilis from Southern Africa - Dixon, Russell Bruce (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Giant kingfish Caranx ignobilis, the largest species in the family Carangidae, are global icons as apex marine predators. They are widespread in tropical to subtropical regions globally, where they are of high importance to ecosystems and fisheries. During summer, adults aggregate for spawning, making them vulnerable to overfishing. The world's largest recorded C. ignobilis aggregation is in southern Mozambique. Some of these aggregating individuals (an unknown proportion) have been recorded passing into South African waters. Furthermore, a unique aggregation of adult C. ignobilis in South Africa's Mtentu Estuary has attracted global attention but remains unexplained, hence warranting investigation. Research on C. ignobilis globally has shown relatively small home ranges. Research in southern Africa has been limited and inconclusive. Thus, the broad aim of this study is to describe the movement patterns of C. ignobilis from southern Africa. Long-term (36 years) mark-recapture data from the Oceanographic Research Institute's Co-operative Fish Tagging Project, comprising 3 729 tagged C. ignobilis and 144 recaptures, were analysed. While 74% of recaptures were recorded < 1 km from the tagging location, long-distance movements of up to 419 km were also recorded (mean = 15 km). Although adults moved significantly (p < 0.01) greater distances than juveniles, they also displayed high levels of site fidelity. Seasonal trends included evidence of a summer migration; however, there was still considerable uncertainty regarding exact movements. Therefore, 43 C. ignobilis were acoustically tagged and subsequently monitored along the east coast for over five years with the Acoustic Tracking Array Platform's passive receiver array. All acoustically tagged adult C. ignobilis migrated to southern Mozambique each year (with minor exceptions), from distances of up to 632 km. When not migrating, South African-based fish showed consistent inter-annual fidelity to individual home ranges. Although coastal home range length (excluding migrations) varied considerably between individuals, even the mean length (92 km) was greater than any previously recorded C. ignobilis home range, globally. In contrast to the southern Mozambique aggregation, the Mtentu Estuary aggregation seems to comprise of individuals showing fidelity to that region. The passive tracking of eight acoustically tagged individuals in the Mtentu Estuary revealed clear trends. Statistical modelling showed that estuarine presence was strongly associated with periods of cold coastal upwelling. Diel movement patterns showed that the utilisation of warm surface waters ~ 4 km upstream during the day was followed by nightly departures to the mouth or sea. Thus, it is likely that this majestic aggregation is for thermal refuge; specifically, for daily re-warming after feeding in cold waters at night. Findings from this study are of global ecological interest and have direct applications for local fisheries management and the development of sustainable eco-tourism. Protecting these vulnerable aggregations is of the utmost importance for the future of this species in southern Africa.
Keywords: Caranx -- Africa, Southern; Caranx -- Migration; Underwater acoustic telemetry; Carangidae -- Africa, Southern; Fish tagging